Association of endothelial glycocalyx shedding and coronary microcirculation assessed by an angiography-derived index of microcirculatory resistance in patients with suspected coronary artery disease - Liu, Yang; Chen, Si; Liu, Shaoyan; Sun, Guoqiang; Sun, Zhijun; Liu, Hongbin (Frontiers in Cardiovascular Medicine, 2022)
Background: The endothelial glycocalyx (EG) is essential for maintaining microvascular homeostasis. However, the relationship between the EG and coronary microcirculation remains to be elucidated. The main component of the EG is syndecan-1, and its shedding has been claimed to represent the state of the EG. In this study, we aimed to analyze the association between syndecan-1 and the coronary microcirculation. Methods: We enrolled suspected coronary artery disease (CAD) patients who consecutively underwent coronary angiography (CAG) and angiography-based analysis of physiological indices in the left anterior descending artery (LAD). Serum syndecan-1 was measured by enzyme-linked immunosorbent assay (ELISA). The coronary microcirculation was evaluated by the presence of coronary microvascular dysfunction (CMD) and an impaired microvascular vasodilatory capacity (IMVC), which were quantified by an angiography-derived index of microcirculatory resistance (IMRangio) in the maximum hyperemic state (H-IMRangio) induced by adenosine triphosphate and the ratio (RRRangio) of IMRangio in the nonhyperemic phase to H-IMRangio, respectively. Results: A total of 528 patients were enrolled in this study. There was no difference in epicardial coronary complexity between patients with high syndecan-1 (HSG) and low syndecan-1 (LSG) levels grouped by the median concentration of syndecan-1 (SYNTAX: 7[3,10] vs. 9[4,12], P=0.15). However, H-IMRangio and RRRangio were different between the LSG and HSG groups (H-IMRangio: 23.64±6.28 vs. 27.67±5.59, P<0.01; RRRangio: 1.74[1.46,2.08] vs. 1.55[1.34,1.72], P<0.01). Patients with CMD (H-IMRangio >25) and patients with IMVC (RRRangio below the median value) both had higher syndecan-1 levels (CMD: 86.44±54.15 vs. 55.2±43.72, P<0.01; IMVC: 83.86±55.41 vs. 59.68±45.06, P<0.01). After adjustment for confounding factors, HSG remained associated with the presence of CMD and IMVC (CMD: odds ratio [OR]: 2.769, P<0.01; IMVC: OR: 1.908, P<0.01). Conclusion: High levels of syndecan-1 are independently associated with the presence of CMD and IMVC among patients with suspected CAD.